Terapi Bekam untuk Pengobatan bagi Penderita Tekanan Darah Tinggi: Studi Takhrij dan Syarah Hadis - Al-Muhasibi, Naufal Abid (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss cupping therapy for the treatment of high blood pressure sufferers. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study indicate that the quality status of the hadith regarding cupping therapy for treatment for patients with high blood pressure is considered authentic based on the takhrij hadith. Syarah hadith shows that cupping therapy contains drugs and the best treatment in preventing and curing disease, especially for people with high blood pressure, one of the factors that causes high blood pressure is a substance called toxic, with cupping therapy having a suction method and inhaled, the toxic substances in the body will come out so that blood pressure returns to normal. The conclusion of this study is that the hadith regarding cupping therapy is acceptable so that it can be used as a practice for Muslims and also becomes an effective alternative treatment option, especially for people with high blood pressure.